Informational Capabilities : The Missing Link for the Impact of ICT on Development - Gigler, Bjorn-Soren (World Bank, Washington, DC, 2014)
Under what conditions can information and communications technologies (ICTs) enhance the well-being of poor communities? The paper designs an alternative evaluation framework (AEF) that applies Sen's capability approach to the study of ICTs in order to place people's well-being, rather than technology at the center of the study. The AEF develops an impact chain that examines the mechanisms by which access to, and meaningful use of, ICTs can enhance peoples, 'informational capabilities' and can lead to improvements in people's human and social capabilities. This approach thus uses peoples human capabilities, rather than measures of access or usage, as its principal evaluative space. Based on empirical evidence from rural communities uses of ICTs in Bolivia, the study concludes that enhancing people's informational capabilities is the most critical factor determining the impact of ICTs on their well-being. The findings indicate that improved informational capabilities, like literacy, do enhance the human capabilities of the poor and marginalized to make strategic life choices to achieve the lifestyle they value. Evaluating the impact of ICTs in terms of capabilities thus reveals that there is no direct relationship between improved access to, and use of, ICTs and enhanced well-being; ICTs lead to improvements in people's lives only when informational capabilities are transformed into expanded human and social capabilities in the economic, political, social, organizational and cultural dimensions of their lives.